Nanoconfined Bulk-Gas Transport Behavior over a Wide Range of Knudsen Number - Yi Zhang (Geofluids)
Shale matrix, located at Guizhou Province, is rich in nanopores, and gas slippage takes place during shale gas development, resulting in inapplicability of the classical Navier-Stokes equation. Investigation of gas transmission mechanism in nanoscale is helpful to reach a clear understanding of shale gas production performance. On the basis of the Knudsen number, the gas flow mechanism is divided into continuous flow, slippage flow, transition flow, and Knudsen diffusion. Notably, the accurate characterization of transition flow is still challenging up to date. Although there are many established models, they either fail to cover all the flow mechanisms or contain many fitting parameters, the determination of which requires a large number of experimental and molecular simulation data, limiting application of the existing models. Therefore, establishment of bulk-gas transport model over a wide range of Knudsen number without fitting parameters is urgent. First of all, existed theoretical models are compared, and the advantages and disadvantages of previous contributions are analyzed. Weight factors of Knudsen diffusion and slippage flow are obtained, respectively, according to Knudsen’s model and Wu’s model. Then, a model, free of empirical coefficients, is proposed. After that, effects of pore size, reservoir pressure, and temperature on transmission capacity are investigated. As the proposed model does not contain fitting parameters and remains high accuracy over a wide range of Knudsen number, it shares broad application potential, like shale gas production prediction, reserve estimation in Guizhou Province.